Polymerase Chain Reaction for detection of Streptococcus mutans and Streptococcus sobrinus in dental plaque of children from Cartagena, Colombia (Colombia Medica, 2024)
Objectives: To detect the presence of Streptococcus mutans and Streptococcus sobrinus in dental plaque of children from Cartagena and correlate it to dental caries precavity stages, applying a standardized PCR-based technique for epidemiological purposes.Methods: Descriptive study using a non-probabilistic sample of 50 children between 3 and 5 years of age, preschoolers from a Caribbean population in Colombia. Criteria for selection were that children should exhibit plaque accumulations on the surface of the cervical margins of the rearmost molars, and placed in one of two study groups: carious lesions and sound surfaces. Dental plaque samples from both groups were subjected to molecular analysis and statistical analysis was applied to determine the difference between the two groups using the frequencies of presence of S. mutans, S. sobrinus or both in thetwo groups applying Fisher’s exact test for association between the presence of microorganisms and the state of the tooth surface from where the dental plaque was taken.Results: The frequency of S. mutans in carious lesions was 76% and 24% in healthy surfaces. The frequency of S. sobrinus in carious lesions was 81.9% and 18.1% in caries-free surfaces. There was statistical significance between the presence of S. mutans and the presence of caries (p=0.001) and between the presence of S. sobrinus (p=0.02) and the presence of caries.There was no statistical significance between the presence of caries and the simultaneous presence of both microorganisms (p=0.08).Conclusions: The presence of S. mutans and S. sobrinus in dental plaque samples is highly prevalent and associated to non cavitated carious lesions, being the molecular identification of these microorganisms by PCR a sensitive, fast, and easy to use detection method for the mutans group of oral bacteria.